PENGARUH STABILISASI MENGGUNAKAN POLYPROPYLENE FIBER TERHADAP TANAH LEMPUNG EKSPANSIF - Dianita Dianita; Sri Wulandari (Universitas Gunadarma, 2023)
Expansive clay soil is a land having the nature plasticity high when things are changing the system of ground water levels. The expansive loam if there is an increase in the moisture content of soil will spread abroad accompanied by the increase of water pressure the pressure development and emergence. An effort to improving fisis mechanical parameters and land to land stabilization will use of stabilization. This research to test the land of the clay done stabilization used polypropylene fiber to analyze the effect of the density of the stabilized soil and analyze the variation of the most optimal polypropylene fiber content used. Polypropylene is one of the kind of plastic that most often used as a fiber and have sifat-sifat can dissolve in organic compounds, stand the heat, has a tenuous, high are not poisonous, resistant to chemicals. The soil samples taken from the Hambalang village, west java. Testing done on land with a mixture of polypropylene fiber % 0,25, % 0,5, 0,75 % and 1 % with waiting time 7 day and 14 day. Optimum use of polypropylene fiber as a mixture of occurring at the level of the index 0,5% is 19,69% of plasticity the soil shear strength is 1,098 kg/cm2, primary settlement is 1,47 mm and maximum dry weight is 1,453 g/cm3 .